Modified Julia Olefination on Sugar‐Derived Lactones: Synthesis of Difluoro‐exo‐glycals. Issue 4 (22nd December 2014) - Habib, Samuel; Gueyrard, David
Abstract: We report the preparation of difluoro‐ exo ‐glycals by gem ‐difluoroolefination of benzylated sugar‐derived lactones using a modified Julia reaction. The addition is highly stereoselective, and the Smiles‐rearrangement–elimination sequence can be carried out under microwave irradiation. Abstract : We report the preparation of difluoro‐ exo ‐glycals by olefination of sugar‐derived lactones using a modified Julia reaction.